Evaluation of dimethylacetamide and dimethylformamide as cryoprotectants for epididymal alpaca sperm (Vicugna pacos) - Contreras, Winnie (2020)
The aim of this study was to determine the effect of the type (dimethylacetamide [DMA] and dimethylformamide [DMF]) and concentrations (1, 3.5, 7%) of cryoprotective agents on three sperm parameters during the cryopreservation process of epididymal alpaca sperm. A 2x3 factorial design consisting of the two cryoprotectants and the three concentrations was used. The parameters of sperm viability (SYBR-14/PI) and mitochondrial membrane potential (MitoTracker Deep Red FM) of sperm of 40 epididymis were evaluated by flow cytometry and motility by microscopy after thawing. 111/5000. A higher percentage of motility after thawing was found with AMD (14%) than with DMF (10%) (p=0.001). In addition, there was a significant effect of the cryoprotectant concentration in all the parameters evaluated (p<0.001), being better at concentrations of 1 and 3.5% than with 7%. No significant effect of the cryoprotectant-concentration interaction was found.